2021
DOI: 10.18517/ijaseit.11.4.12172
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Classification Method in Menu Engineering Using the K-Nearest Neighbors Algorithm

Abstract: In the culinary business, the menu is crucial; therefore, the performance of each menu needs to be known to maintain business continuity. Menu engineering is a special technique used to see the performance comparison of each menu item. This research proposes modeling menu engineering with a new approach in classifying menu items using the k-Nearest Neighbors (k-NN) algorithm using the sales training data of sales data in 2019 belonging to one of the micro, small and medium-sized enterprises in the culinary sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The cluster output is used to create strategic recommendations for the menu to increase sales. Setiyawati [1] also proposed an engineering menu model using the K-Nearest Neighbors Algorithm. The findings of this study suggested a new approach to engineering menu analysis using a classification of menu items according to the characteristics of the menu mix and item contribution margin.…”
Section: Fig 1 Menu Engineering Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The cluster output is used to create strategic recommendations for the menu to increase sales. Setiyawati [1] also proposed an engineering menu model using the K-Nearest Neighbors Algorithm. The findings of this study suggested a new approach to engineering menu analysis using a classification of menu items according to the characteristics of the menu mix and item contribution margin.…”
Section: Fig 1 Menu Engineering Matrixmentioning
confidence: 99%
“…The menu is one of the most fundamental aspects of business continuity in the culinary industry [1], [2]. A welldesigned and managed menu could generate greater profit for the business and provide product information to consumers [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used texture features include Local Binary Pattern [12]- [14] and GLCM [6], [15], [16]. Furthermore, classification frequently applied using the method of KNN [12], [17], ANN [18], [19], SVM [20], [21], and Naïve Bayes [22], [23].…”
Section: Introductionmentioning
confidence: 99%